A distributed and interconnected network of sensors for environmental radiological monitoring. (December 2020) - Gallego Manzano, L.; Bisegni, C.; Boukabache, H.; Curioni, A.; Heracleous, N.; Murtas, F.; Perrin, D.; Silari, M.
Abstract: The W-MON project aims to improve and automatize the control of the presence of radioactive material in conventional waste containers at CERN using a distributed network of interconnected low-power radiation sensors. The key development is the integration of a lightweight but sensitive radiation sensor in a powerful network that allows continuous data recording, transfer and storage in a database for alarm triggering and subsequent data analysis. The Chiyoda D-shuttle personal dosimeter was used as proof-of-concept. Extensive tests performed with the commercial version of the D-shuttle showed that its robustness, stability under variable thermal conditions, high sensitivity and hourly dose logging capabilities make it a strong candidate for the project. To comply with the requirements of remote operation and wireless data transmission to a central server, a customized version of the D-shuttle has been developed. Two additional radiation sensors are also currently being considered. The sensors have been coupled to a custom-made communication board allowing for long-range low-power LoRa wireless data transmission. A centralized IoT (Internet of Things) end-to-end data architecture has been developed for real-time monitoring and visualization of the radiation level in waste containers before the final integration into REMUS, the overall CERN Radiation and Environment Monitoring Unified Supervision service. Highlights: Environmental radiological monitoring for conventional waste. Lightweight and smart radiation sensors for real-time monitoring of the radiation level in waste containers. Distributed network of interconnected low-power radiation sensors with LoRa wireless data transmission.